2016
DOI: 10.1071/rdv28n2ab210
|View full text |Cite
|
Sign up to set email alerts
|

210 Post-Translational Modification of Histone H4 Acetylation During in Vitro Maturation of Canine Oocytes

Abstract: Proper in vitro oocyte maturation, crucial for in vitro fertilisation, is poorly understood and inefficient in dogs. Post-translational modifications of histones are involved in the meiotic process and preparation of oocytes for fertilisation. The present study aimed to evaluate post-translational histone H4 acetylation at lysine 12 (H4K12ac) and 16 (H4K16ac) in canine oocytes during in vitro maturation (IVM). Ovaries were retrieved from 1–7 year-old bitches undergoing routine ovariohysterectomy (OH). Grade I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Global deacetylation has been described during the progression of meiosis in mice (Akiyama et al., , ; De La Fuente et al., ; Kim et al., ; Manosalva & Gonzalez, ; Spinaci et al., ), pigs (Endo et al., ; Wang, ; Wang et al., ), cows (Maalouf et al., ; Racedo et al., ), horses (Franciosi et al., ) and humans (van den Berg et al., ). As for canine oocytes, we have demonstrated in a previous study that other lysine residues, namely H4K12 and H4K16, were also deacetylated after the resumption of meiosis (Motheo et al., ). Interestingly, similar findings were described in the present study, where we observed a significant decrease in fluorescence intensity of H4K5 between immature and post‐IVM canine oocytes.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Global deacetylation has been described during the progression of meiosis in mice (Akiyama et al., , ; De La Fuente et al., ; Kim et al., ; Manosalva & Gonzalez, ; Spinaci et al., ), pigs (Endo et al., ; Wang, ; Wang et al., ), cows (Maalouf et al., ; Racedo et al., ), horses (Franciosi et al., ) and humans (van den Berg et al., ). As for canine oocytes, we have demonstrated in a previous study that other lysine residues, namely H4K12 and H4K16, were also deacetylated after the resumption of meiosis (Motheo et al., ). Interestingly, similar findings were described in the present study, where we observed a significant decrease in fluorescence intensity of H4K5 between immature and post‐IVM canine oocytes.…”
Section: Discussionmentioning
confidence: 77%
“…On average, only 15–20% of the canine oocytes are capable of resuming meiosis and achieving metaphase II (MII) after 48–72 hr of in vitro culture (Songsasen & Wildt, ). Many factors are attributed to such low efficiency, such as the uniqueness of the canine reproductive physiology, hormonal environment, role of the oviduct on oocyte maturation, oocyte morphology and metabolism, and incorrect gene activity and epigenetic marks during the IVM process (Apparício et al., ; Luvoni, Chigioni, Allievi, & Macis, ; Motheo et al., ; Songsasen & Wildt, ).…”
Section: Introductionmentioning
confidence: 99%